Investigation of the thiol-disulfide system state of rats with encephalopathy caused by the effect of antituberculous drugs - A. V. Levich; N. O. Skorokhodova; D. H. Zhyvytsia; Yu. V. Prosvetov (Patologìâ)
Objective. To determine in an experimental study the nature of changes in the status of the thiol-disulfide system of rats with encephalopathy, due to the influence of complex of anti-tuberculosis drugs for the treatment of chemoresistant tuberculosis and the possibility of their drug correction with the use of ademetionine 1,4-butanedisulfonate.